High-accuracy design for mesh antennas considering the metallic mesh. (15th July 2022) - Zhang, Jun; He, Baiyan; Nie, Rui; Wang, Guobiao; Zhang, Lianhong; Yu, Hongbo; Ma, Xiaofei
Highlights: A cable-membrane coupling model is proposed to account for the compatible deformation between the cable network and the metallic mesh. By introducing the topology matrix of the cable-membrane structure, the unified equilibrium equation of the mesh antenna is established and solved by the dynamic relaxation method. A novel high-accuracy design method for the mesh antenna is proposed by optimising the geometric dimensions of the cables and the membranes. Abstract: Metallic meshes have great effects on the surface accuracy and tension distribution of mesh antennas, which present considerable challenges to the high-accuracy design of reflectors. Unfortunately, the metallic mesh is usually neglected in current research due to the complex coupling between the metallic mesh and the cable network. This paper presents a novel high-accuracy design method for the mesh reflector considering the effect of the metallic mesh. A cable-membrane coupling model is first proposed to account for the compatible deformation between the cable network and the metallic mesh. By introducing the topology matrix of the cable-membrane structure, the unified equilibrium equation of the mesh antenna is established and solved by the dynamic relaxation (DR) method. A novel high-accuracy design method for the mesh antenna is proposed by optimising the geometric dimensions of the cables and the membranes. Finally, this method is effectively applied to the high-accuracy design of two mesh antennas with different topologies considering the effect of the metallic mesh. The superiority of the method is demonstrated through a comparison with the literature, and the accuracy of the results is exhibited by the FEM software ABAQUS. Graphical abstract: Image, graphical abstract